(untitled) (Research, Society and Development, 2021)
Objective: To analyze the laterality of quilombola children and its relationship with motor development. Methodology: This is an exploratory, observational, analytical, descriptive and cross-sectional study, with a quantitative and qualitative approach, carried out in the quilombola community of Tiningu, Santarém-Pará. The sample consisted of 18 children of both genders aged between 7 and 11 years. As a data collection instrument, an EDM proposed by Rosa Neto (2002) was used. Data were tabulated and according to the proposal of Rosa Neto (2002) and underwent simple descriptive statistical analysis in Microsoft Office Excele 2010 and BioEstat version 5.0. Results and discussion: The age group in greater quantity is concentrated in the ages of 10 to 11 years. The laterality results show that the majority of children (72.22%) were complete right-handed, (27.78%) loss of indefinite laterality and no children presented sinister or crossed laterality. Conclusion: It is important to analyze the laterality of children because from these skills, they can master their movements and know themselves and the world around them. Carrying out similar studies, with representatives, taking data that draw attention to a broader view of laterality in children, such as prevention and intervention of probable distortions in the learning process.